Costa Rican university entrepreneurial ecosystem and its link with the entrepreneurial intention: an exploratory study - Herrera-Valverde, Daniela; Mora-Esquivel, Ronald; Leiva, Juan Carlos (Tec Empresarial, 2020)
The literature on entrepreneurial university ecosystems has being evidence of possible factors related to entrepreneurial intention, however, there is still a significant information gap. This article seeks to provide a conceptual model that integrates various components of a university entrepreneurial ecosystem that could be related to entrepreneurial intention. The qualitative exploratory study, based on 10 in-depth interviews with professionals linked to entrepreneurial activity in 10 universities, public and private of Costa Rica, poses six pillars: curriculum design, co-curricular activities, organizational infrastructure, strategic commitment, the allocation of financial resources and the participation of global academic and entrepreneurship networks. Also, define technology as a transversal axis. The study confirms, from the point of view of the interviewees, that may exist a link between a set of pillars and their components with the entrepreneurial intention. It highlights the strategic alignment of the universities, the promotion of an entrepreneurial culture, the value of co-curricular activities, the teaching role and the articulation with the national ecosystem.